Analisis Nilai Tambah Pengolahan Beras Merah Menjadi Bubuk Beras Merah : Studi Kasus Industri Rumah Tangga KWT Bungi Jaya di Kabupaten Muna - Windy Febrianto; Abdul Gafaruddin; La Ode Kasno Arif (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Red rice is one of the most popular staple foods in Southeast Asia. In Indonesia, it is an alternative staple food to white rice, known for its high nutritional value. In addition to containing carbohydrates, fats, proteins, fiber, and minerals, red rice is also rich in anthocyanins, which function as antioxidants. This study aims to analyze the added value and its distribution created from processing red rice into Moreha Wuna red rice powder in the home industry of KWT Bungi Jaya, located in Bungi Village, Kontunaga Subdistrict, Muna Regency. The research was conducted in November 2022. The study area was chosen based on the consideration that KWT Bungi Jaya is the only home industry producing Moreha Wuna red rice powder in Muna Regency. The respondent in this research was the owner of the home industry. The analysis employed the Hayami method for added value analysis. The results showed that the added value obtained from processing red rice into Moreha Wuna red rice powder in the KWT Bungi Jaya home industry was Rp63,212 per kilogram of raw material. Consequently, the monthly added value from this home industry was Rp758,544. The distribution of added value from the red rice processing included the owner's profit of Rp46,562 (73.66%) and labor compensation of Rp16,650 (26.33%).